Metode Pembelajaran Bahasa Arab Bagi Kelas Intensif MA Attanwir Bojonegoro (Studi Analisis Kelas 1 Intensif MA Attanwir Bojonegoro) - Latifah, Siti Nurul Aini (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
The Intensive Class is one of the special classes at MA Attanwir Bojonegoro, because this Intensive class is aimed at prospective students who will enter MA Attanwir Bojonegoro, the education and teaching uses a collaborative curriculum between the Islamic boarding school curriculum and the national curriculum. The aim of this research is to find out the Arabic language learning method for class 1 of the Intensive MA Attanwir Bojonegoro, and to find out the obstacles faced by students when learning Arabic and efforts to overcome them. This research is qualitative research that uses data collection techniques, observation, interviews and documentation. Data analysis was carried out using the Miles and Hubermen data analysis model. This model consists of data collection, data reduction, data presentation, and drawing conclusions or validation. The results of the research show that 1) the Arabic language learning method for class 1 of the Intensive MA Attanwir Bojonegoro uses 3 learning methods, namely, the direct method, the drill method, and the lecture method, 2) the problems faced by the students of class 1 of the Intensive MA Attanwir Bojonegoro, namely, from the different educational backgrounds of students, lack of motivation in Arabic, and from social environmental factors. 3) efforts made to overcome it; provides basic Arabic language material juz 1 whose learning material is the same as class 1 MTs, and in implementing learning educators require memorization, provide motivation and support to students, and familiarize themselves with Arabic in class or what is often called Muhawaroh (conversation in Arabic) before learning begins, and there are also Muhadloroh activities which are held every Thursday after learning hours end.